Maruti's Nexa – enhancing customer experience beyond buying. Issue 4 (8th July 2020) - Kaushik, Arun Kumar; Mohan, Geetha
Abstract : Research methodology: The case collates secondary data pertaining to Maruti's current position, Nexa, the premium retail sales channel of Maruti, and recent developments in the Indian automobile industry. It presents the facts and data published on websites, newspapers and magazines in the form of a case study. Case overview/synopsis: Nexa was launched by Maruti in 2015 to enhance the buying experience of its premium customers and to re-position itself as a premium brand. It started offering customized services to car purchasers through its well-trained employees, attractive store environment and omni channel experience. Through all these facilities, though Nexa had a bumpy ride for selling its first product, it managed to pace up and perform better in the next few years. It remained to be seen how Maruti would handle competitor and cost challenges and how it would strategize its efforts to strengthen its footprint in the Indian automotive industry. Complexity academic level: This case can be used in retail management, sales and distribution management, marketing management and related courses/modules at the master's level.